Post Covid-19 Pandemic Digital Marketing Communications Strategy (Case Study At PT Matahari Dept Store Grand Mal Bekasi) - Venny Lestari; Hartono Hartono; Endah Fantini (LPPM Universitas PGRI Sumatera Barat, 2024)
Matahari Grand Mal Bekasi is one of the retail outlets in Indonesia. The purpose of this research is to understand the marketing communication strategies employed by Matahari Grand Mal Bekasi in marketing its products and to identify the marketing communication process at Matahari Grand Mal Bekasi. This research uses a qualitative descriptive research method with data collection through observation, interviews, and documentary study. The theory utilized in this research is integrated marketing communication theory. The results of this research indicate that integrated marketing communication instruments are the strategies employed by Matahari Grand Mal Bekasi in marketing its products. These marketing communication instruments include sales promotions, direct marketing, public relations & publicity, and interactive marketing. The marketing communication process at Matahari Grand Mal Bekasi varies according to the integrated marketing communication instruments used. The marketing communication strategies implemented by Matahari Grand Mal Bekasi demonstrate its success in marketing its products post-COVID-19 pandemic.